2018
DOI: 10.1037/neu0000428
|View full text |Cite
|
Sign up to set email alerts
|

Reading in developmental prosopagnosia: Evidence for a dissociation between word and face recognition.

Abstract: Adult developmental prosopagnosics read as quickly and fluently as controls, while they are seemingly unable to learn efficient strategies for recognizing faces. We suggest that this is due to the differing demands that face and word recognition put on the perceptual system. (PsycINFO Database Record

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…This comparison is particularly interesting as the DPs performed the exact same tests as did the HP group, and in many respects seem to pose a mirror image of the HPs. In the first section below, we present the results for the group comparisons, which for the most part have been reported elsewhere (Gerlach et al, 2017Starrfelt et al, 2018). The dissociations analyses, however, have not been presented previously.…”
Section: Do Low-performers Differ Qualitatively From Others In Face Pmentioning
confidence: 99%
See 2 more Smart Citations
“…This comparison is particularly interesting as the DPs performed the exact same tests as did the HP group, and in many respects seem to pose a mirror image of the HPs. In the first section below, we present the results for the group comparisons, which for the most part have been reported elsewhere (Gerlach et al, 2017Starrfelt et al, 2018). The dissociations analyses, however, have not been presented previously.…”
Section: Do Low-performers Differ Qualitatively From Others In Face Pmentioning
confidence: 99%
“…The control sample comprised 20 individuals. Note that data from these participants have been reported in previous publications (Gerlach, Klargaard, Petersen, & Starrfelt, 2017;Starrfelt, Klargaard, Petersen, & Gerlach, 2018). They are included here for a direct comparison with the HPs included in the present study.…”
Section: Low Performers (Developmental Prosopagnosics (Dp))mentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of the face recognition disorder in such individuals can be as severe as that noted in individuals with a frank RH VOTC lesion and, like those individuals, These individuals rely on voice and other cues such as hairstyle to support individual face recognition Barton, Albonico, Susilo, Duchaine, & Corrow, 2019;Rosenthal et al, 2017). In contrast with the association of word and face recognition deficits in DD, as reviewed in Shared Representations With Weighting section above, there are now several studies of individuals with CP which have demonstrated a dissociation between face and word recognition (Burns et al, 2017;Rubino, Corrow, Corrow, Duchaine, & Barton, 2016;Starrfelt, Klargaard, Petersen, & Gerlach, 2018).…”
Section: Patients With a Selective Impairment Of Either Face Or Word mentioning
confidence: 99%
“…The results above are consistent with intermingling but distinct neural resources underlying the processing of different categories (Plaut & Behrmann, ). For single faces and words, such intermingling has been previously suggested by fMRI (Mei et al, ; Nestor et al, ) and neuropsychological studies (Albonico & Barton, ; Gerlach, Marstrand, Starrfelt, & Gade, ; Sigurdardottir, Ívarsson, Kristinsdóttir, & Kristjánsson, , but see Starrfelt, Klargaard, Petersen, & Gerlach, ). Moreover, prior EEG work has documented the reliance of these two categories on occipitotemporal channels around 170 ms as reflected, for instance, by the importance of the N170 ERP component for faces (Bentin, Allison, Puce, Perez, & McCarthy, ; Ince et al, ; Rossion, Joyce, Cottrell, & Tarr, ), words (Bentin, Mouchetant‐Rostaing, Giard, Echallier, & Pernier, ; Maurer, Zevin, & McCandliss, ), and, more generally, for visual expertise (Tanaka & Curran, ).…”
Section: Discussionmentioning
confidence: 54%